GENETIC POLYMORPHISM OF LOCI DETERMINING BREAD MAKING QUALITY IN UKRAINIAN WHEAT VARIETIES - S. V. Chebotar; E. M. Blagodarova; E. A. Kurakina; I. V. Semenyuk; A. M. Polishchuk; N. A. Kozub; I. A. Sozinov; A. N. Khokhlov; A. I. Ribalka; Yu. M. Sivolap (Вавиловский журнал генетики и селекции)
The paper presents an overview of studies of genetic polymorphism of loci determining bread-making quality among Ukrainian wheat varieties by means of electrophoretic analysis of storage proteins (Gli and  Glu) and PCR. The results of analysis of polymorphism in the Gli-A1, Gli-B1, Gli-D1, Glu-A3 loci, as well as the allelic compositions of the Pina-D1 and Pinb-D1 genes, determining grain hardness, and Wx genes, controlling amylose content in the starch of the endosperm, are presented. Comparison of the results obtained with allele-specific primers to the γ gliadin loci and by storage protein electrophoresis shows that the former method can identify some alleles, but the level of polymorphism revealed by this method is lower than that revealed by electrophoresis of storage proteins. Most of the varieties under consideration have PCR alleles characteristic for hard wheat, and only three varieties have alleles specific for soft wheat. Varieties originating from different Ukrainian breeding-centers differ in grain hardness. PCR analysis has not revealed the presence of null alleles of Wx genes in the studied Ukrainian genetic pool but allowed selection of breeding material for further development of low-amylose varieties.